Symmetric orthogonal polynomials and the associated orthogonal L-polynomials - Ranga, A. Sri [UNESP] (1995)
We show how symmetric orthogonal polynomials can be linked to polynomials associated with certain orthogonal L-polynomials. We provide some examples to illustrate the results obtained. Finally as an application, we derive information regarding the orthogonal polynomials associated with the weight function. © 1995 American Mathematical Society.